2011
DOI: 10.1021/es201858r
|View full text |Cite
|
Sign up to set email alerts
|

Liquid CO2 Displacement of Water in a Dual-Permeability Pore Network Micromodel

Abstract: Permeability contrasts exist in multilayer geological formations under consideration for carbon sequestration. To improve our understanding of heterogeneous pore-scale displacements, liquid CO(2) (LCO(2))-water displacement was evaluated in a pore network micromodel with two distinct permeability zones. Due to the low viscosity ratio (logM = -1.1), unstable displacement occurred at all injection rates over 2 orders of magnitude. LCO(2) displaced water only in the high permeability zone at low injection rates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
146
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(160 citation statements)
references
References 49 publications
11
146
1
1
Order By: Relevance
“…The viscosity ratio is defined as the ratio of the advancing non-wetting fluid viscosity to the defending wetting fluid viscosity (η w ), i.e., M = η n /η w . In addition, recent laboratory studies [41][42][43][44] have shown the strong influence of subcore scale heterogeneities on steady-state migration patterns, spatial distributions, and fluid saturations. To gain a better understanding of pore-scale two-phase displacement mechanisms, a series of numerical simulations are conducted to study the effect of Ca and M on displacement stability and fluid saturation in a homogeneous and a heterogeneous pore networks, and the obtained results are compared to indicate the effect of media heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…The viscosity ratio is defined as the ratio of the advancing non-wetting fluid viscosity to the defending wetting fluid viscosity (η w ), i.e., M = η n /η w . In addition, recent laboratory studies [41][42][43][44] have shown the strong influence of subcore scale heterogeneities on steady-state migration patterns, spatial distributions, and fluid saturations. To gain a better understanding of pore-scale two-phase displacement mechanisms, a series of numerical simulations are conducted to study the effect of Ca and M on displacement stability and fluid saturation in a homogeneous and a heterogeneous pore networks, and the obtained results are compared to indicate the effect of media heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 2(a) a spurious loop is clearly evident for t D = 0.2 and even for t D = 0.14 a tiny loop can be seen. Similarly, Figure 2(b) shows results for the same parameters but using equation (4). In this case the loop is formed earlier: already by time t D = 0.1 a very significant loop is in evidence 3 .…”
Section: Numerical Results For Original Systemmentioning
confidence: 76%
“…In addition, having more points to describe the foam front ensures a less jagged 4 There is a special rule that is used to subdivide the topmost front segment which arises due to the very high curvatures that can occur on the top boundary: see [11] for details.…”
Section: Modifying Velocity For Concavities and Regridding The Frontmentioning
confidence: 99%
See 2 more Smart Citations